Analysis of Paragraphs in the Written Works of Students XI SMK Muhammadiyah Pangkalan Bun - Sari, Khoyiroh Novita; Nasucha, Yakub (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2024)
Paragraph writing is an important element in written works that determines the quality of writing through the cohesion and interrelationship between paragraphs. However, there are still many students who have difficulty in determining the location of the main sentence and the right paragraph development pattern in their written work. Therefore, this study aims to: (1) to identify the forms of paragraphs in the written works of students in grade XI of SMK Muhammadiyah Pangkalan Bun and (2) to describe the paragraph development patterns found in the written works of students in grade XI of SMK Muhammadiyah Pangkalan Bun. The results show that there are four kinds of paragraphs based on the location of the main sentence, namely (1) the main sentence is at the beginning of the paragraph (deductive) totaling 27 paragraphs, (2) the main sentence is at the end of the paragraph (inductive) totaling 14 paragraphs, (3) the main sentence is at the beginning and end of the paragraph (mixed) totaling 2 paragraphs, and (4) without the main sentence totaling 7 paragraphs. In addition, there are six paragraph development patterns found, namely (1) comparison and contrast totaling 10 paragraphs, (2) analogy totaling 1 paragraph, (3) examples totaling 1 paragraph, (4) cause and effect totaling 29 paragraphs, (5) definition totaling 7 paragraphs, and (6) classification totaling 2 paragraphs. From these results, it can be concluded that the most dominant paragraph development pattern is the cause and effect pattern, while the most common main sentence location is at the beginning of the paragraph (deductive). This research is expected to provide a better understanding for teachers and students in writing good and correct paragraphs, so that the quality of students' written work can improve.